ERRORS IN THE DIRECT TRANSLATION OF PHRASEOLOGICAL UNITS AND WAYS TO PREVENT THEM - Toxirova Madinabonu Abdumo‘min qizi (Bright Mind Publishing, 2025)
The article examines primary errors that occur in the direct translation of phraseological units and methods for their prevention. The study suggests effective translation strategies considering cultural and linguistic characteristics of idiomatic expressions.
Keywords: Phraseological units, translation errors, translation methods, cultural context, linguistic features.